Assessing the requirements from 'BB101' 2006 and 2018 for a naturally ventilated preparatory school in the UK. (September 2019) - Ji, Yingchun; Swan, Will; Fitton, Richard; Fernando, Terrence
In the UK, BB101 is the guidance document for ventilation design of school buildings. There are significant changes proposed in the new version of BB101. The aim of this paper is to examine the requirements of thermal comfort and CO2 -based indoor air quality using both versions on a typical naturally ventilated preparatory school design using dynamic thermal simulations. The findings indicate that the new set of requirements on this school building design (both thermal and CO2 concentration) are much more difficult to meet than the requirements from the old version. One of the new thermal comfort criteria may be too difficult to achieve in practice, as the target value was exceeded for all the rooms of the examined design, using both test reference year and design summer year weather data. The ventilation provision for the school design is believed to be adequate. With appropriate ventilation control strategies, the design is able to meet the revised CO2 concentration criteria. Further examinations of the criteria from the new guidance document are needed to make sure the chosen criteria are fit for purpose. The use of future projected design summer year weather data (2020) also adds extra challenges for the preparatory school building to meet the newly proposed adaptive thermal comfort criteria. Practical applications: The research presents a very first assessment of a preparatory school building design using the newly proposed BB101 guidance document. It will assist further exploration on the appropriateness of the new assessment criteria and the use of design summer year weather data in order to explore the implications of the new BB101 guidelines for designers. The method adopted in the research can also be used for other building types to assess overheating in buildings when adaptive comfort criteria are recommended.